2016
DOI: 10.1371/journal.pone.0149448
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Kidney Disease and Diabetic Retinopathy in Patients with Type 2 Diabetes

Abstract: PurposeTo explore the relationship between chronic kidney disease (CKD) and diabetic retinopathy (DR) in a representative population of type 2 diabetes mellitus (DM2) patients in Catalonia (Spain).MethodsThis was a population-based, cross-sectional study. A total of 28,344 patients diagnosed with DM2 who had recorded ophthalmologic and renal functional examinations were evaluated. Data were obtained from a primary healthcare electronic database of medical records. CKD was defined as an estimated glomerular fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
50
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 33 publications
5
50
0
Order By: Relevance
“…[4][5][6][7][8]10,19,21,22,24,28,30,34,[38][39][40][42][43][44][47][48][49][50][51][52][53] 69 This is consistent with other genome-wide association studies in Caucasian and Mexican-American patients. 70,71 As the relationship between genetic polymorphisms and diabetic retinopathy is still a new and emerging field, some studies have demonstrated new associations between single nucleotide polymorphisms, but these studies have not yet been replicable.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…[4][5][6][7][8]10,19,21,22,24,28,30,34,[38][39][40][42][43][44][47][48][49][50][51][52][53] 69 This is consistent with other genome-wide association studies in Caucasian and Mexican-American patients. 70,71 As the relationship between genetic polymorphisms and diabetic retinopathy is still a new and emerging field, some studies have demonstrated new associations between single nucleotide polymorphisms, but these studies have not yet been replicable.…”
supporting
confidence: 89%
“…48 These findings were corroborated by Penno et al 49 who reported that a high urine albumin-to-creatinine ratio of ≥300 mg/g was associated with diabetic retinopathy (OR=2.9; 95% CI, 2.1-4.0). Likewise, Rodríguez-Poncelas et al 50 found that increasing urine albumin-to-creatinine ratio was significantly correlated with rising diabetic retinopathy prevalence, and this association was significant even at urine albumin-to-creatinine levels of ≥10 mg/g (OR=1.2; 95% CI, 1.1-1.4).…”
Section: Chronic Kidney Diseasementioning
confidence: 93%
“…It is characterized by increased serum creatinine levels, persistent albuminuria, and decreased glomerular filtration rates. Previous studies have shown that albuminuria and a low estimated glomerular filtration rate (eGFR) were both risk factors for DR. [3][4][5][6][7] However, most previous studies were cross-sectional, not longitudinal. As for DME, only limited studies have reported its association with renal function.…”
mentioning
confidence: 99%
“…To date, many studies have reported UACR cut-off values for diseases that are associated with diabetic diabetes, e.g., MA cut-offs of 19.25 mg/g Cr [19] for hypertension; 10.7 mg/g Cr [20], 15.6 mg/g Cr [21], 10.7 mg/g Cr [22], and 10.0 mg/g Cr [23] for diabetic retinopathy (DR); and 4.8 mg/g Cr [6] for metabolic syndrome. However, only four studies that investigated the cut-off values for type 2 diabetes [15], CKD [16], and DN [17,18] have been conducted.…”
Section: Uacr Cut-off Values For Diseases Associated With Diabetesmentioning
confidence: 99%